Abonos orgánicos en la producción de pepino (Cucumis satius l.) En la zona de Buena Fe - Burgos Véliz, Kleber Klender (2015)
The study was conducted in the area of Buena Fe Los Rios province at the "Eglantine" geographically located 0 ° 57 '24' 'south latitude and 79 ° 27' 02 '' west longitude at an altitude of 100 m The objectives were: the determination of organic fertilizers in the production of cucumber (Cucumis sativus L.), in the area of Buena Fe, lasting 75 days, a complete block design Random (RCBD) was used, using, three organic fertilizers and four repetitions. Plant height at 15 cm 65.49 reported on water hyacinth; 30 days 112.39 cm humus and 45 days reached the highest values in the treatment Gallinaza 143.62 cm. In the treatment chicken manure used as many flowers was achieved with 25.94; and as much fruit in the same treatment reported cucumbers 11.46. The greatest long fruit was registered with 22.92 cm manure treatment; while fruit diameter greater value was obtained in treatment Water Hyacinth 23.14 cm. The highest values in fruit weight and yield were achieved in the manure treatment with 437.54 g for fruit weight and yield 9.52 kg. The greatest benefit cost ratio was obtained in the treatment humus 0.13.